High resolution X-ray and NMR structural study of human T-cell immunoglobulin and mucin domain containing protein-3. Issue 1 (December 2018) - Gandhi, Amit; Kim, Walter; Sun, Zhen-Yu; Huang, Yu-Hwa; Bonsor, Daniel; Sundberg, Eric; Kondo, Yasuyuki; Wagner, Gerhard; Kuchroo, Vijay; Petsko, Gregory; Blumberg, Richard
Abstract T-cell immunoglobulin and mucin domain containing protein-3 (TIM-3) is an important immune regulator. Here, we describe a novel high resolution (1.7 Å) crystal structure of the human (h)TIM-3 N-terminal variable immunoglobulin (IgV) domain with bound calcium (Ca++ ) that was confirmed by nuclear magnetic resonance (NMR) spectroscopy. Significant conformational differences were observed in the B-C, C′-C″ and C′-D loops of hTIM-3 compared to mouse (m)TIM-3, hTIM-1 and hTIM-4. Further, the conformation of the C-C′ loop of hTIM-3 was notably different from hTIM-4. Consistent with the known metal ion-dependent binding of phosphatidylserine (PtdSer) to mTIM-3 and mTIM-4, the NMR spectral analysis and crystal structure of Ca++ -bound hTIM-3 revealed that residues in the hTIM-3 F-G loop coordinate binding to Ca++ . In addition, we established a novel biochemical assay to define hTIM-3 functionality as determined by binding to human carcinoembryonic antigen cell adhesion molecule 1 (CEACAM1). These studies provide new insights useful for understanding and targeting hTIM-3.